Immunoproteomics and Surfaceomics of the Adult Tapeworm Hymenolepis diminuta - Młocicki, Daniel; Sulima, Anna; Bień, Justyna; Näreaho, Anu; Zawistowska-Deniziak, Anna; Basałaj, Katarzyna; Sałamatin, Rusłan; Conn, David Bruce; Savijoki, Kirsi (Frontiers in Immunology, 2018)
In cestodiasis, mechanical and molecular contact between the parasite and the host activates the immune response of the host and may result in inflammatory processes, leading to ulceration and intestinal dysfunctions. The aim of the present study was to identify antigenic proteins of the adult cestode Hymenolepis diminuta by subjecting the total protein extracts from adult tapeworms to 2DE immunoblotting (two-dimensional electrophoresis combined with immunoblotting) using sera collected from experimentally infected rats. A total of thirty-six protein spots cross-reacting with the rat sera were identified using LC-MS/MS. As a result, sixty-eight proteins, including certain structural muscle proteins (actin, myosin and paramyosin) and moonlighters (heat shock proteins, kinases, phosphatases and glycolytic enzymes) were identified; most of which were predicted to possess binding and/or catalytic activity required in various metabolic and cellular processes, and reported here as potential antigens of the adult cestode for the first time. As several of these antigens can also be found at the cell surface, the surface-associated proteins were extracted and subjected to in-solution digestion for LC-MS/MS identification (surfaceomics). As a result, a total of 76 proteins were identified, from which 31 proteins, based on 2DE immunoblotting, were predicted to be immunogenic. These included structural proteins actin, myosin and tubulin) and certain moonlighting proteins (heat-shock chaperones) while enzymes with diverse catalytic activities were found as the most dominating group of proteins. Thus, the present study suggests that the H. diminuta somatic proteins exposed to the host possess antigenic properties and belong to variouis groups our findings also suggest that the immune response of the host during the adult cestode infection could be stimulated by diverse mechanisms, involving proteins entering the host body via yet unknown non-classical mechanism(s). In conclusion, the present study shed more light into the complexity of the enteric cestodiasis, and suggests that the H. diminuta somatic proteins exposed to the host possess immunomodulatory functions, and that the immune response of the host is stimulated by diverse mechanisms, involving proteins entering the host body via yet unknown non-classical mechanism(s).